Global economic changes, skills and international competitiveness. - SINGH, Ajit (1994)
Outlines significant changes in the world economy, and looks at how they relate to the new technological revolution in information and communications. Sresses the importance of advanced skills in developing national technological capacities and in reducing the North-South gap.